Transforming growth factor- b stimulates Interleukin-11 production by human periodontal ligament and gingival fibroblasts - R. Yashiro (journal of clinical periodontology, 2006)
Background: Transforming growth factor (TGF)-b is a potent multifunctional polypeptide, abundant in the bone matrix. Interleukin (IL)-11 is a pleiotropic cytokine with effects on multiple cell types. The present study was performed to evaluate the regulatory effects of TGF-b on IL-11 production by human periodontal ligament cells (PDL) and human gingival fibroblasts (HGF). Material and Methods: The expression of TGF-b receptor in PDL and HGF were observed using flow cytometry. PDL and HGF were stimulated with TGF-b with or without protein kinase C (PKC) inhibitors and activator. IL-11, bone morphogenetic protein-2 (BMP-2) and TGF-b mRNA expression was quantified by real-time polymerase chain reaction (PCR). IL-11 production was measured using enzymelinked immunosorbent assay. Results: PDL and HGF expressed both TGF-b receptor I and TGF-b receptor II on the cell surfaces. IL-11 mRNA expression and IL-11 production were augmented by TGFb in both PDL and HGF, with higher values in PDL. PKC inhibitors partially suppressed TGF-b-induced IL-11 production in PDL and HGF, whereas activator enhanced it. TGF-b mRNA and BMP-2 mRNA expression were up-regulated by TGF-b in PDL. Conclusion: These results suggest that PDL produce IL-11 in response to TGF-b.